2011
DOI: 10.1002/sca.20283
|View full text |Cite
|
Sign up to set email alerts
|

Holographic otoscope for nanodisplacement measurements of surfaces under dynamic excitation

Abstract: Summary We describe a novel holographic otoscope system for measuring nano-displacements of objects subjected to dynamic excitation. Such measurements are necessary to quantify the mechanical deformation of surfaces in mechanics, acoustics, electronics, biology and many other fields. In particular, we are interested in measuring the sound-induced motion of biological samples, such as an eardrum. Our holographic otoscope system consists of laser illumination delivery (IS), optical head (OH), and image processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Our group has been studying the sound-induced motion of the TM using fiber-optic-based opto-electronic holographic (OEH) interferometery (Furlong and Pryputniewicz, 1998;Furlong et al, 2009;Hern andez-Montes et al, 2009;Flores-Moreno et al, 2011). Our previous studies have shown that sound-induced motions of the mammalian TM follow different patterns (simple, complex, ordered) within different stimulus frequency ranges .…”
Section: B Measurements Of the Magnitude And Phase Angle Of Tm Motionmentioning
confidence: 99%
“…Our group has been studying the sound-induced motion of the TM using fiber-optic-based opto-electronic holographic (OEH) interferometery (Furlong and Pryputniewicz, 1998;Furlong et al, 2009;Hern andez-Montes et al, 2009;Flores-Moreno et al, 2011). Our previous studies have shown that sound-induced motions of the mammalian TM follow different patterns (simple, complex, ordered) within different stimulus frequency ranges .…”
Section: B Measurements Of the Magnitude And Phase Angle Of Tm Motionmentioning
confidence: 99%
“…The temporal bones were then mounted on a 3D positioner placed on a vibration-isolated table, which also supported multiple lasers and optical devices needed for the holographic measurements (Hern andez-Montes et al, 2009;Flores-Moreno et al, 2011). The bones were positioned such that the planes of their tympanic rings were parallel to the holographic recording CCD camera, and the TM image was centered in the camera plane.…”
Section: A Preparation and The Use Of Human Temporal Bonesmentioning
confidence: 99%
“…Typically, each laser pulse has a duration of 2% to 5% of the period of the tonal stimulus. 11,18 This generates the same effect as a strobe light by only capturing the motion of the TM at desired phases of the stimulus wave.…”
Section: Stroboscopic Measurements Of Displacementmentioning
confidence: 99%
“…[4][5][6] Therefore, full-field-of-view techniques are required to quantify shape, sound-induced displacements, and mechanical properties of the TM. [7][8][9] In our previous works, [10][11][12] we have reported holographic interferometric measurements of sound-induced displacements over a majority of the surface of mammalian TMs. A potential criticism of these measurements is that the displacements were measured only along one direction that was along the normal vector to the tympanic ring.…”
Section: Introductionmentioning
confidence: 99%